Kebiasaan Sarapan, Jajan, dan Membawa Bekal Siswa Sekolah Dasar di Kota Bogor: Breakfast, Snacking, and Bringing Lunch Habits of Elementary School Students in Bogor City - Ekayanti, Ikeu; Roosita, Katrin; Anggiruling, Dwikani Oklita; Adha, As Syaffa Amalia (Departemen Gizi Masyarakat, Fakultas Ekologi Manusia, IPB dan PERGIZI PANGAN Indonesia, 2025)
The purpose of this study is to analyze the relationship between breakfast habits, the habit of bringing lunch, and the habit of snacks at school in elementary school students in Bogor City. This study uses a cross-sectional study design. This study uses primary data from a total of 1167 students in 161 schools in Bogor City. The study's results showed that 59.1% of students always had breakfast, 36.6% sometimes had breakfast, and 4.3% never had breakfast. The main reasons for not eating breakfast were school attendance (58.6%) and lack of appetite (42.8%). Most students (89.0%) consumed rice/noodles/porridge/bread at breakfast, with only 4.9% consuming all five food groups. The habit of snacking shows that 73.6% of students always snack. The most consumed snacks are manufactured food/beverages (81.3%) and wet/traditional cakes (71.8%). The habit of bringing lunch to children shows that 22.5% of students always bring lunch with 38.7% using it as a substitute for breakfast. Parental education significantly correlated with breakfast frequency (p=0.000) and breakfast food diversity (p=0.031). Pocket money had a significant relationship with the diversity of snacks (p=0.002) and a negative relationship with the habit of bringing lunch (p=0.021). Breakfast habits showed a positive relationship with bringing lunch and snacks (p=0.000). Most students always have breakfast, but the food options are not diverse. The habit of snacking has become a culture for students, students who eat breakfast or bring lunch tend to continue to make snacks at school.